Pengembangan E-Modul Etnomatematika Menggunakan Metode Aglile Scrum - Rudy Hartono; Okta Kamiksius; Nolly Pialewi; Herji (BETRIK, 2026)
One of the primary objectives of mathematics education in schools is to enhance students’ thinking skills. In the context of deep learning-based instruction, teachers are required to deliver learning materials contextually, particularly in ethnomathematics, by connecting mathematical concepts with local cultural practices and utilizing technology as a supporting learning medium. This study aims to develop a web-based ethnomathematics e-module as an alternative instructional resource that is more contextual, interactive, and flexible. The research employs a Research and Development (R&D) approach, with system development carried out using the Agile Scrum methodology. The development process involves the preparation of a Product Backlog and the implementation of Scrum Events through multiple iterative sprints. The system is developed using the Laravel framework, supported by MySQL as the database, and Bootstrap to ensure a responsive user interface. System testing is conducted using the Black Box Testing method, involving teachers and 28 students as users. The results indicate that all system features function properly in accordance with user requirements. Furthermore, the developed system supports a more interactive learning process, facilitates teachers in delivering contextualized materials, and enhances students’ understanding through evaluation features equipped with immediate feedback.